Antibacterial linear pull rope material for tampons and preparation method of antibacterial linear pull rope material

Through the combination technology of modified nano titanium dioxide, PET resin and composite emulsion, the problem of insufficient antibacterial properties of tampon linear drawstrings is solved, and efficient antibacterial and anti-fouling properties are achieved, ensuring the safety of tampons during use. and comfort.

CN119265936APending Publication Date: 2025-01-07YOULIMEI (HUBEI) TECH CO LTD
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411583159.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-07
Publication Date
2025-01-07

AI Technical Summary

Technical Problem

The tampons on the market have insufficient antibacterial properties in linear draw ropes, which leads to bacteria prone to breeding in the wet and hot environment of the vagina, which may cause vaginal infection.

Method used

Using the combined technology of modified nanotitanium dioxide, PET resin and composite emulsion, antibacterial fibers are prepared through the action of crosslinking agents epoxychlorohydrin, polyguanidine, citronellol and polypyrrole to improve the antibacterial, antistatic and antifouling of fibers. and enhance the binding strength and dispersion of antibacterial agents through melt blending and spinning techniques.

Benefits of technology

It significantly improves the antibacterial performance of the tampon linear drawstring, ensures that it still has good antibacterial effect after multiple washes, avoids discomfort caused by static electricity, and improves the anti-fouling performance of the fiber.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005123653090000141
    Figure BDA0005123653090000141
  • Figure BDA0005123653090000142
    Figure BDA0005123653090000142
  • Figure BDA0005123653090000151
    Figure BDA0005123653090000151
Patent Text Reader

Abstract

The invention discloses an antibacterial linear pull rope material for tampons and a preparation method thereof.The preparation method comprises the steps that polyguanidine salt with an antibacterial function is grafted to the surface of nano titanium dioxide under the action of a cross-linking agent epichlorohydrin, then a modified nano titanium dioxide antibacterial agent and PET resin are subjected to melt blending and then spinning, and the antibacterial linear pull rope material is obtained. The antibacterial performance of the fiber material is improved; according to the composite emulsion provided by the invention, 3, 5-bis (trifluoromethyl) styrene is adopted to replace traditional styrene, so that the anti-fouling performance of fibers is improved; meanwhile, polypyrrole is introduced into the composite emulsion, so that the antistatic performance of the fiber is improved, and discomfort brought by static electricity to people is avoided; under the action of a cross-linking agent genipin, the bonding strength between the antibacterial fiber and the composite emulsion coating is improved, the composite emulsion coating is not prone to falling off, and the fiber material still has good antistatic and anti-pollution performance after being washed for multiple times.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of sanitary products, and in particular to an antibacterial straight drawstring material for tampons and a preparation method thereof. Background Art

[0002] Tampons, also known as sanitary plugs, are a kind of cotton cylinder, mainly made of cotton, man-made fiber or a mixture of these two materials, with diameters ranging from 1 cm to 1.9 cm, and a straight drawstring at the end. The convenience of tampons meets the new needs of consumers. Compared with sanitary napkins, women can dress, move, work, exercise, relax, play, etc. freely when using tampons, without suffering from leakage and worry. They are gradually being accepted by domestic consumers, especially young people. When women have their menstrual period, tampons are inserted into the vagina. They have the effect of strongly absorbing menstrual blood. They have attracted much attention because of their small size, comfortable use, and good absorption capacity.

[0003] Most tampons on the market focus on the antibacterial properties of the absorbent core, but ignore the antibacterial properties of the straight drawstring at the tail end. The straight drawstring is in the hot and humid environment of the vagina for a long time, which can easily breed bacteria and cause vaginal infection. Therefore, it is equally important to improve the antibacterial properties of the straight drawstring at the tail end of the tampon. Summary of the invention

[0004] In view of the deficiencies in the prior art, an object of the present invention is to provide an antibacterial straight drawstring material for tampons and a preparation method thereof.

[0005] In order to achieve the above object, the present invention adopts the following technical scheme:

[0006] A method for preparing an antibacterial straight drawstring material for tampons, comprising the following steps:

[0007] S1. Preparation of modified nano titanium dioxide

[0008] The nano-titanium dioxide is dispersed in deionized water, and then polyguanidine salt and epichlorohydrin are added thereto, the pH value of the solution is adjusted to 9-12, and the solution is heated and stirred for reaction. After the reaction is completed, the solution is filtered, washed and dried to obtain the modified nano-titanium dioxide.

[0009] In this step, the mass ratio of nano-titanium dioxide, polyguanidine salt and epichlorohydrin is 10-15:4-8:5-10. In some embodiments of the present invention, for example, 10:4:5, 10:6:8, 10:8:10, 12:4:5, 12:6:8, 12:8:10, 15:4:5, 15:6:8, 15:8:6, 15:8:10 can be selected, but it is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0010] Wherein, the polyguanidine salt is selected from polyhexamethylene biguanide hydrochloride or polyhexamethylene biguanide nitrate.

[0011] In this step, the temperature of the heating and stirring reaction is 60-80°C. In some embodiments of the present invention, for example, 60°C, 65°C, 70°C, 75°C, and 80°C can be selected; the time of the heating and stirring reaction is 3-5h, for example, 3h, 3.5h, 4h, 4.5h, and 5h can be selected; but it is not limited to the listed values, and other values ​​not listed within the numerical range are also applicable.

[0012] In this step, the polyguanidine salt with antibacterial function is grafted onto the surface of the nano-titanium dioxide through the action of the cross-linking agent epichlorohydrin, thereby improving the antibacterial property of the nano-titanium dioxide and also improving the dispersion property of the nano-titanium dioxide in the PET resin.

[0013] S2. Preparation of antibacterial fiber

[0014] The modified nano titanium dioxide, PET resin and compatibilizer are uniformly mixed, granulated by twin-screw extrusion to obtain antibacterial masterbatch, and then melt-spinned to obtain antibacterial fiber.

[0015] In this step, the mass ratio of modified nano titanium dioxide, PET resin and compatibilizer is 15-25:100:5-10. In some embodiments of the present invention, for example, 15:100:5, 15:100:8, 15:100:10, 20:100:5, 20:100:10, 25:100:5, 25:100:10 can be selected, but it is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0016] Wherein, the compatibilizer is selected from EVA-g-MAH.

[0017] In this step, the temperatures of Zone I, Zone II and Zone III of the twin-screw extruder are 240°C, 270°C and 280°C, the temperature of the melting section is 290°C, and the temperature of the die head is 285°C.

[0018] In this step, the modified nano-titanium dioxide antibacterial agent and the PET resin are melt-blended and then spun. On the one hand, the bonding strength between the antibacterial agent and the resin is improved, and on the other hand, the dispersibility of the antibacterial agent in the fiber is also improved. Compared with the post-finishing method, the antibacterial agent is more evenly distributed and more firmly bonded, and it still has good antibacterial properties after multiple washings.

[0019] S3. Preparation of composite fibers

[0020] The antibacterial fiber is immersed in the composite emulsion, and then the immersed fiber is dried to obtain the composite fiber.

[0021] In this step, the preparation method of the composite emulsion is as follows:

[0022] Sodium dodecyl sulfate and tert-dodecyl mercaptan are added to deionized water, stirred evenly, and then nitrogen is introduced to expel the air. Then, butadiene, 3,5-bis(trifluoromethyl)styrene, citronellol and acrylamide are added thereto, and the temperature is raised to 45-55° C. with stirring. Initiator ammonium persulfate is added and the reaction is carried out for 2-4 hours. Then, pyrrole and oxidant ammonium persulfate are added thereto, and the reaction is stirred for 12-18 hours to obtain a composite emulsion.

[0023] Specifically, the mass ratio of sodium dodecyl sulfate, tert-dodecyl mercaptan, deionized water, butadiene, 3,5-bis(trifluoromethyl)styrene, citronellol, acrylamide, initiator ammonium persulfate, pyrrole and oxidant ammonium persulfate is 2-4:1-3:150:15-25:10-20:5-10:10-15:0.5-1:5-10:3-6.

[0024] In this step, the mass ratio of the antibacterial fiber to the composite emulsion is 1:10-15. In some embodiments of the present invention, for example, 1:10, 1:11, 1:12, 1:13, 1:14, 1:15 can be selected, but it is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0025] The composite emulsion provided by the present invention adopts 3,5-bis(trifluoromethyl)styrene to replace traditional styrene, and introduces fluorine-containing functional groups into the composite emulsion, thereby improving the anti-fouling performance of the fiber; at the same time, citronellol is introduced into the composite emulsion through the addition of double bonds, and citronellol is a natural polymer compound with good antibacterial properties and high safety, thereby further improving the antibacterial performance of the fiber; in addition, the present invention also introduces polypyrrole into the composite emulsion, thereby improving the antistatic performance of the fiber and avoiding the discomfort caused by static electricity to people.

[0026] S4. Preparation of cross-linked composite fibers

[0027] The composite fiber is immersed in a genipin solution, then taken out and subjected to a heat curing treatment to obtain a cross-linked composite fiber.

[0028] In this step, the mass ratio of the composite fiber to the genipin solution is 1:15-25. In some embodiments of the present invention, for example, 1:15, 1:18, 1:20, 1:22, 1:25 can be selected, but it is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0029] Wherein, the mass fraction of the genipin solution is 0.4-0.6%.

[0030] In this step, the temperature of the heat curing treatment is 50-70°C. In some embodiments of the present invention, for example, 50°C, 55°C, 60°C, 65°C, and 70°C can be selected; the time of the heat curing treatment is 2-3h. In some embodiments of the present invention, for example, 2h, 2.5h, and 3h can be selected; but it is not limited to the listed values, and other values ​​not listed within the numerical range are also applicable.

[0031] In this step, the amino groups in the antibacterial fiber and the amino groups in the composite latex coating are chemically cross-linked through the action of the cross-linking agent genipin, thereby improving the bonding strength between the antibacterial fiber and the composite latex coating. The composite latex coating is not easy to fall off, and after multiple washings, the fiber material still has good antistatic and anti-fouling properties.

[0032] S5. Preparation of antibacterial straight draw rope material

[0033] The cross-linked composite fiber is spun and twisted to obtain the antibacterial straight draw rope material.

[0034] In this step, the cross-linked composite fiber is spun and twisted using existing technology, and the twisting degree can be selected according to actual needs, which is not limited here.

[0035] The present invention also provides an antibacterial straight drawstring material for tampons prepared by the above preparation method.

[0036] Compared with the prior art, the present invention has the following beneficial effects:

[0037] (1) The present invention firstly grafts polyguanidine salt with antibacterial function onto the surface of nano-titanium dioxide through the action of cross-linking agent epichlorohydrin, thereby improving the antibacterial property of nano-titanium dioxide and also improving the dispersion property of nano-titanium dioxide in PET resin; then, the modified nano-titanium dioxide antibacterial agent and PET resin are melt-blended and then spun, which, on the one hand, improves the bonding strength between the antibacterial agent and the resin, and on the other hand, improves the dispersion property of the antibacterial agent in the fiber. Compared with the post-finishing method, the antibacterial agent is more evenly distributed and more firmly bonded, and still has good antibacterial property after multiple washings.

[0038] (2) The composite emulsion provided by the present invention adopts 3,5-bis(trifluoromethyl)styrene to replace traditional styrene, and improves the anti-fouling performance of the fiber by introducing fluorine-containing functional groups into the composite emulsion; at the same time, citronellol is introduced into the composite emulsion through the addition of double bonds. Citronellol is a natural polymer compound with good antibacterial properties and high safety, which further improves the antibacterial performance of the fiber; in addition, the present invention also introduces polypyrrole into the composite emulsion, which improves the antistatic performance of the fiber and avoids the discomfort caused by static electricity.

[0039] (3) The amino groups in the antibacterial fiber and the amino groups in the composite latex coating are chemically cross-linked through the action of the cross-linking agent genipin, which improves the bonding strength between the antibacterial fiber and the composite latex coating. The composite latex coating is not easy to fall off. After multiple washings, the fiber material still has good antistatic and anti-fouling properties. DETAILED DESCRIPTION

[0040] The present invention is further described in detail below through specific preferred embodiments, but the present invention is not limited to the following embodiments.

[0041] It should be noted that, unless otherwise specified, the chemical reagents involved in the present invention were purchased through commercial channels.

[0042] The particle size of the nano titanium dioxide used in the present invention is 40-60nm;

[0043] PET resin, CAS number: 25038-59-9, purchased from Hubei Shineng Chemical Technology Co., Ltd.;

[0044] The model of EVA-g-MAH is PX1164, which was purchased from Shanghai Beidaer New Materials Co., Ltd.

[0045] Example 1

[0046] A method for preparing an antibacterial straight drawstring material for tampons, comprising the following steps:

[0047] S1. Disperse 10 g of nano titanium dioxide in 150 mL of deionized water, then add 4 g of polyhexamethylene biguanide hydrochloride and 5 g of epichlorohydrin, adjust the pH of the solution to 10, heat and stir at 60 ° C for 5 h, and after the reaction is completed, filter, wash and dry to obtain modified nano titanium dioxide;

[0048] S2, 15 parts of modified nano titanium dioxide, 100 parts of PET resin and 5 parts of compatibilizer EVA-g-MAH were mixed uniformly, and granulated by twin-screw extruder, the temperatures of zone I, zone II and zone III of the twin-screw extruder were 240°C, 270°C and 280°C, the temperature of the melting section was 290°C, and the temperature of the die head was 285°C to obtain antibacterial masterbatch, and then melt spinning was performed to obtain antibacterial fiber;

[0049] S3, immersing 1 kg of antibacterial fiber in 10 kg of composite emulsion for 2 hours, and then drying the immersed fiber to obtain composite fiber;

[0050] Wherein, the preparation method of the composite emulsion is as follows:

[0051] 2 g of sodium dodecyl sulfate and 1 g of tert-dodecyl mercaptan are added to 150 g of deionized water and stirred evenly. Then, nitrogen is introduced to expel the air. Then, 15 g of butadiene, 10 g of 3,5-bis(trifluoromethyl)styrene, 5 g of citronellol and 10 g of acrylamide are added thereto. The mixture is stirred and heated to 50° C., 0.5 g of initiator ammonium persulfate is added thereto, and the reaction is carried out for 3 h. Then, 5 g of pyrrole and 3 g of oxidant ammonium persulfate are added thereto, and the reaction is stirred for 12 h to obtain a composite emulsion.

[0052] S4, immersing 1 kg of the composite fiber in 15 kg of a 0.5 wt% genipin solution for 2 h, then taking it out and heat curing it at 50° C. for 3 h to obtain a cross-linked composite fiber;

[0053] S5. Spinning and twisting the cross-linked composite fiber to obtain an antibacterial straight draw rope material.

[0054] Example 2

[0055] A method for preparing an antibacterial straight drawstring material for tampons, comprising the following steps:

[0056] S1. Disperse 15 g of nano titanium dioxide in 150 mL of deionized water, then add 8 g of polyhexamethylene biguanide hydrochloride and 10 g of epichlorohydrin, adjust the pH of the solution to 10, heat and stir the reaction at 80 ° C for 3 h, and after the reaction is completed, filter, wash and dry to obtain modified nano titanium dioxide;

[0057] S2, 25 parts of modified nano titanium dioxide, 100 parts of PET resin and 10 parts of compatibilizer EVA-g-MAH are mixed uniformly, and granulated by twin-screw extruder, the temperatures of zone I, zone II and zone III of the twin-screw extruder are 240°C, 270°C and 280°C, the temperature of the melting section is 290°C, and the temperature of the die head is 285°C to obtain antibacterial masterbatch, and then melt spinning is performed to obtain antibacterial fiber;

[0058] S3, immersing 1 kg of antibacterial fiber in 15 kg of composite emulsion for 2 hours, and then drying the immersed fiber to obtain composite fiber;

[0059] Wherein, the preparation method of the composite emulsion is as follows:

[0060] 4 g of sodium dodecyl sulfate and 3 g of tert-dodecyl mercaptan are added to 150 g of deionized water and stirred evenly. Then, nitrogen is introduced to expel the air. Then, 25 g of butadiene, 15 g of 3,5-bis(trifluoromethyl)styrene, 8 g of citronellol and 12 g of acrylamide are added thereto. The mixture is stirred and heated to 50° C., 1 g of initiator ammonium persulfate is added thereto, and the reaction is carried out for 3 h. Then, 8 g of pyrrole and 5 g of oxidant ammonium persulfate are added thereto, and the reaction is stirred for 12 h to obtain a composite emulsion.

[0061] S4, immersing 1 kg of the composite fiber in 20 kg of a 0.4 wt% genipin solution for 2 h, then taking it out and heat curing it at 70° C. for 2 h to obtain a cross-linked composite fiber;

[0062] S5. Spinning and twisting the cross-linked composite fiber to obtain an antibacterial straight draw rope material.

[0063] Example 3

[0064] A method for preparing an antibacterial straight drawstring material for tampons, comprising the following steps:

[0065] S1. Disperse 12 g of nano titanium dioxide in 150 mL of deionized water, then add 6 g of polyhexamethylene biguanide hydrochloride and 8 g of epichlorohydrin, adjust the pH of the solution to 12, heat and stir at 70 ° C for 4 h, and after the reaction is completed, filter, wash and dry to obtain modified nano titanium dioxide;

[0066] S2, 20 parts of modified nano titanium dioxide, 100 parts of PET resin and 8 parts of compatibilizer EVA-g-MAH are mixed evenly, and granulated by twin-screw extrusion, the temperatures of zone I, zone II and zone III of the twin-screw extruder are 240°C, 270°C and 280°C, the temperature of the melting section is 290°C, and the temperature of the die head is 285°C to obtain antibacterial masterbatch, and then melt spinning is performed to obtain antibacterial fiber;

[0067] S3, immersing 1 kg of antibacterial fiber in 12 kg of composite emulsion for 2 hours, and then drying the immersed fiber to obtain composite fiber;

[0068] Wherein, the preparation method of the composite emulsion is as follows:

[0069] 3 g of sodium dodecyl sulfate and 2 g of tert-dodecyl mercaptan are added to 150 g of deionized water and stirred evenly. Then, nitrogen is introduced to expel the air. Then, 20 g of butadiene, 20 g of 3,5-bis(trifluoromethyl)styrene, 10 g of citronellol and 15 g of acrylamide are added thereto. The mixture is stirred and heated to 50° C., 0.8 g of initiator ammonium persulfate is added thereto, and the reaction is carried out for 3 h. Then, 10 g of pyrrole and 6 g of oxidant ammonium persulfate are added thereto, and the reaction is stirred for 12 h to obtain a composite emulsion.

[0070] S4, immersing 1 kg of the composite fiber in 25 kg of a 0.4 wt% genipin solution for 2 h, then taking it out and heat curing it at 70° C. for 2 h to obtain a cross-linked composite fiber;

[0071] S5. Spinning and twisting the cross-linked composite fiber to obtain an antibacterial straight draw rope material.

[0072] Example 4

[0073] A method for preparing an antibacterial straight drawstring material for tampons, comprising the following steps:

[0074] S1. Disperse 12 g of nano titanium dioxide in 150 mL of deionized water, then add 8 g of polyhexamethylene biguanide hydrochloride and 10 g of epichlorohydrin, adjust the pH of the solution to 12, heat and stir at 60 ° C for 5 h, and after the reaction is completed, filter, wash and dry to obtain modified nano titanium dioxide;

[0075] S2, 22 parts of modified nano titanium dioxide, 100 parts of PET resin and 6 parts of compatibilizer EVA-g-MAH are mixed uniformly, and granulated by twin-screw extruder, the temperatures of zone I, zone II and zone III of the twin-screw extruder are 240°C, 270°C and 280°C, the temperature of the melting section is 290°C, and the temperature of the die head is 285°C to obtain antibacterial masterbatch, and then melt spinning is performed to obtain antibacterial fiber;

[0076] S3, immersing 1 kg of antibacterial fiber in 15 kg of composite emulsion for 2 hours, and then drying the immersed fiber to obtain composite fiber;

[0077] Wherein, the preparation method of the composite emulsion is as follows:

[0078] 3 g of sodium dodecyl sulfate and 3 g of tert-dodecyl mercaptan are added to 150 g of deionized water, stirred evenly, and then nitrogen is introduced to expel the air. Then, 18 g of butadiene, 18 g of 3,5-bis(trifluoromethyl)styrene, 6 g of citronellol and 12 g of acrylamide are added thereto, the temperature is raised to 50° C. with stirring, 0.8 g of initiator ammonium persulfate is added thereto, and the reaction is carried out for 4 h. Then, 6 g of pyrrole and 4 g of oxidant ammonium persulfate are added thereto, and the reaction is stirred for 12 h to obtain a composite emulsion.

[0079] S4, immersing 1 kg of the composite fiber in 15 kg of a 0.6 wt% genipin solution for 2 h, then taking it out and heat curing it at 70° C. for 2 h to obtain a cross-linked composite fiber;

[0080] S5. Spinning and twisting the cross-linked composite fiber to obtain an antibacterial straight draw rope material.

[0081] Comparative Example 1

[0082] A method for preparing an antibacterial straight drawstring material for tampons, comprising the following steps:

[0083] S1. 15 parts of nano titanium dioxide, 100 parts of PET resin and 5 parts of compatibilizer EVA-g-MAH are mixed uniformly, and granulated by twin-screw extruder. The temperatures of zone I, zone II and zone III of the twin-screw extruder are 240°C, 270°C and 280°C, the temperature of the melting section is 290°C, and the temperature of the die head is 285°C to obtain antibacterial masterbatch, and then melt spinning is performed to obtain antibacterial fiber;

[0084] S2, immersing 1 kg of antibacterial fiber in 10 kg of composite emulsion for 2 hours, and then drying the immersed fiber to obtain composite fiber;

[0085] Wherein, the preparation method of the composite emulsion is as follows:

[0086] 2 g of sodium dodecyl sulfate and 1 g of tert-dodecyl mercaptan are added to 150 g of deionized water and stirred evenly. Then, nitrogen is introduced to expel the air. Then, 15 g of butadiene, 10 g of 3,5-bis(trifluoromethyl)styrene, 5 g of citronellol and 10 g of acrylamide are added thereto. The mixture is stirred and heated to 50° C., 0.5 g of initiator ammonium persulfate is added thereto, and the reaction is carried out for 3 h. Then, 5 g of pyrrole and 3 g of oxidant ammonium persulfate are added thereto, and the reaction is stirred for 12 h to obtain a composite emulsion.

[0087] S3, immersing 1 kg of the composite fiber in 15 kg of a 0.5 wt% genipin solution for 2 h, then taking it out and heat curing it at 50° C. for 3 h to obtain a cross-linked composite fiber;

[0088] S4, spinning and twisting the cross-linked composite fiber to obtain an antibacterial straight draw rope material.

[0089] Compared with Example 1, Comparative Example 1 does not perform modification treatment on the nano-titanium dioxide.

[0090] Comparative Example 2

[0091] A method for preparing an antibacterial straight drawstring material for tampons, comprising the following steps:

[0092] S1. Disperse 10 g of nano titanium dioxide in 150 mL of deionized water, then add 4 g of polyhexamethylene biguanide hydrochloride and 5 g of epichlorohydrin, adjust the pH of the solution to 10, heat and stir at 60 ° C for 5 h, and after the reaction is completed, filter, wash and dry to obtain modified nano titanium dioxide;

[0093] S2, 15 parts of modified nano titanium dioxide, 100 parts of PET resin and 5 parts of compatibilizer EVA-g-MAH were mixed uniformly, and granulated by twin-screw extruder, the temperatures of zone I, zone II and zone III of the twin-screw extruder were 240°C, 270°C and 280°C, the temperature of the melting section was 290°C, and the temperature of the die head was 285°C to obtain antibacterial masterbatch, and then melt spinning was performed to obtain antibacterial fiber;

[0094] S3, immersing 1 kg of antibacterial fiber in 10 kg of composite emulsion for 2 hours, and then drying the immersed fiber to obtain composite fiber;

[0095] Wherein, the preparation method of the composite emulsion is as follows:

[0096] 2 g of sodium dodecyl sulfate and 1 g of tert-dodecyl mercaptan are added to 150 g of deionized water, stirred evenly, and then nitrogen is introduced to expel the air. Then, 15 g of butadiene, 10 g of styrene, 5 g of citronellol and 10 g of acrylamide are added thereto, the temperature is raised to 50°C with stirring, 0.5 g of initiator ammonium persulfate is added thereto, and the reaction is carried out for 3 h. Then, 5 g of pyrrole and 3 g of oxidant ammonium persulfate are added thereto, and the reaction is stirred for 12 h to obtain a composite emulsion.

[0097] S4, immersing 1 kg of the composite fiber in 15 kg of a 0.5 wt% genipin solution for 2 h, then taking it out and heat curing it at 50° C. for 3 h to obtain a cross-linked composite fiber;

[0098] S5. Spinning and twisting the cross-linked composite fiber to obtain an antibacterial straight draw rope material.

[0099] Compared with Example 1, Comparative Example 2 uses styrene to replace 3,5-bis(trifluoromethyl)styrene.

[0100] Comparative Example 3

[0101] A method for preparing an antibacterial straight drawstring material for tampons, comprising the following steps:

[0102] S1. Disperse 10 g of nano titanium dioxide in 150 mL of deionized water, then add 4 g of polyhexamethylene biguanide hydrochloride and 5 g of epichlorohydrin, adjust the pH of the solution to 10, heat and stir at 60 ° C for 5 h, and after the reaction is completed, filter, wash and dry to obtain modified nano titanium dioxide;

[0103] S2, 15 parts of modified nano titanium dioxide, 100 parts of PET resin and 5 parts of compatibilizer EVA-g-MAH were mixed uniformly, and granulated by twin-screw extruder, the temperatures of zone I, zone II and zone III of the twin-screw extruder were 240°C, 270°C and 280°C, the temperature of the melting section was 290°C, and the temperature of the die head was 285°C to obtain antibacterial masterbatch, and then melt spinning was performed to obtain antibacterial fiber;

[0104] S3, immersing 1 kg of antibacterial fiber in 10 kg of composite emulsion for 2 hours, and then drying the immersed fiber to obtain composite fiber;

[0105] Wherein, the preparation method of the composite emulsion is as follows:

[0106] 2 g of sodium dodecyl sulfate and 1 g of tert-dodecyl mercaptan were added to 150 g of deionized water and stirred evenly. Then, nitrogen was introduced to expel the air. Then, 15 g of butadiene, 10 g of 3,5-bis(trifluoromethyl)styrene, 5 g of citronellol and 10 g of acrylamide were added thereto. The mixture was stirred and heated to 50° C., 0.5 g of initiator ammonium persulfate was added, and the reaction was carried out for 3 h to obtain a composite emulsion.

[0107] S4, immersing 1 kg of the composite fiber in 15 kg of a 0.5 wt% genipin solution for 2 h, then taking it out and heat curing it at 50° C. for 3 h to obtain a cross-linked composite fiber;

[0108] S5. Spinning and twisting the cross-linked composite fiber to obtain an antibacterial straight draw rope material.

[0109] Compared with Example 1, in Comparative Example 3, polypyrrole is not introduced into the composite emulsion.

[0110] Comparative Example 4

[0111] A method for preparing an antibacterial straight drawstring material for tampons, comprising the following steps:

[0112] S1. Disperse 10 g of nano titanium dioxide in 150 mL of deionized water, then add 4 g of polyhexamethylene biguanide hydrochloride and 5 g of epichlorohydrin, adjust the pH of the solution to 10, heat and stir at 60 ° C for 5 h, and after the reaction is completed, filter, wash and dry to obtain modified nano titanium dioxide;

[0113] S2, 15 parts of modified nano titanium dioxide, 100 parts of PET resin and 5 parts of compatibilizer EVA-g-MAH were mixed uniformly, and granulated by twin-screw extruder, the temperatures of zone I, zone II and zone III of the twin-screw extruder were 240°C, 270°C and 280°C, the temperature of the melting section was 290°C, and the temperature of the die head was 285°C to obtain antibacterial masterbatch, and then melt spinning was performed to obtain antibacterial fiber;

[0114] S3, immersing 1 kg of antibacterial fiber in 10 kg of composite emulsion for 2 hours, and then drying the immersed fiber to obtain composite fiber;

[0115] Wherein, the preparation method of the composite emulsion is as follows:

[0116] 2 g of sodium dodecyl sulfate and 1 g of tert-dodecyl mercaptan are added to 150 g of deionized water and stirred evenly. Then, nitrogen is introduced to expel the air. Then, 15 g of butadiene, 10 g of 3,5-bis(trifluoromethyl)styrene, 5 g of citronellol and 10 g of acrylamide are added thereto. The mixture is stirred and heated to 50° C., 0.5 g of initiator ammonium persulfate is added thereto, and the reaction is carried out for 3 h. Then, 5 g of pyrrole and 3 g of oxidant ammonium persulfate are added thereto, and the reaction is stirred for 12 h to obtain a composite emulsion.

[0117] S4, spinning and twisting the composite fiber to obtain an antibacterial straight draw rope material.

[0118] Compared with Example 1, Comparative Example 4 does not use the genipin solution for cross-linking.

[0119] The cross-linked composite fibers obtained in Examples 1-4 and Comparative Examples 1-4 were spun, twisted, and woven into fabrics having a gram weight of 205±5 g / m 2 , followed by performance testing, as follows:

[0120] Antibacterial performance test: First, prepare 2×10 5 cfu / ml bacterial suspension (Staphylococcus aureus ATCC6538, Escherichia coli ATCC8099), then place the fabrics to be tested flat in sterile plates, take 0.4mL of bacterial suspension and drop it in the center of the fabrics, spread it evenly, and cover it with a film; place it in an environment of 35℃ and relative humidity of 90% for 24h, then wash it, dilute it (PBS), count it after incubation, and calculate the inhibition rate;

[0121] Surface charge density test: The test is conducted using the charge surface density method in the national standard GB / T 12703.3-2009;

[0122] Anti-fouling performance: tested according to GB / T 30159-2013 standard;

[0123] The test results are shown in Table 1:

[0124] Table 1

[0125]

[0126] The fabric samples obtained in Example 1 and Comparative Example 4 were washed 50 times with standard water, and then the performance test was performed. The standard washing method was as follows: the standard detergent dosage was 2 g / L, the washing condition was 40°C, the washing was performed in a household washing machine, the washing time was 5 minutes, and the samples were dried in an oven at 60°C. A total of 50 washes were performed. The test results are shown in Table 2:

[0127] Table 2

[0128]

[0129]

[0130] Finally, it should be noted that the above embodiments do not limit the present invention in any form. For those skilled in the art, some modifications and improvements can be made to the present invention. Therefore, any modification or improvement made without departing from the spirit of the present invention belongs to the scope of protection claimed in the present invention.

Claims

1. A method for preparing an antibacterial straight drawstring material for tampons, characterized in that: The steps include: S1, dispersing nano titanium dioxide in deionized water, then adding polyguanidine salt and epichlorohydrin thereto, adjusting the pH of the solution to 9-12, heating and stirring to react, and after the reaction is completed, filtering, washing and drying to obtain modified nano titanium dioxide; S2, uniformly mixing the modified nano titanium dioxide, PET resin and compatibilizer, granulating by twin-screw extrusion to obtain antibacterial masterbatch, and then obtaining antibacterial fiber by melt spinning; S3, dipping the antibacterial fiber in the composite emulsion, and then drying the dipped fiber to obtain the composite fiber; S4, immersing the composite fiber in a genipin solution, then taking it out and performing a heat curing treatment to obtain a cross-linked composite fiber; S5. Spinning and twisting the cross-linked composite fiber to obtain an antibacterial straight draw rope material.

2. The preparation method according to claim 1, characterized in that: In step S1, the mass ratio of nano-titanium dioxide, polyguanidine salt and epichlorohydrin is 10-15:4-8:5-10, wherein the polyguanidine salt is selected from polyhexamethylene biguanidine hydrochloride or polyhexamethylene biguanidine nitrate.

3. The preparation method according to claim 1, characterized in that: In step S1, the temperature of the heating and stirring reaction is 60-80°C, and the time of the heating and stirring reaction is 3-5h.

4. The preparation method according to claim 1, characterized in that: In step S2, the mass ratio of modified nano titanium dioxide, PET resin and compatibilizer is 15-25:100:5-10, wherein the compatibilizer is selected from EVA-g-MAH.

5. The preparation method according to claim 1, characterized in that: In step S3, the preparation method of the composite emulsion is as follows: Sodium dodecyl sulfate and tert-dodecyl mercaptan are added to deionized water, stirred evenly, and then nitrogen is introduced to expel the air. Then, butadiene, 3,5-bis(trifluoromethyl)styrene, citronellol and acrylamide are added thereto, and the temperature is raised to 45-55° C. with stirring. Initiator ammonium persulfate is added and the reaction is carried out for 2-4 hours. Then, pyrrole and oxidant ammonium persulfate are added thereto, and the reaction is stirred for 12-18 hours to obtain a composite emulsion.

6. The preparation method according to claim 5, characterized in that: The mass ratio of sodium dodecyl sulfate, tert-dodecyl mercaptan, deionized water, butadiene, 3,5-bis(trifluoromethyl)styrene, citronellol, acrylamide, initiator ammonium persulfate, pyrrole and oxidant ammonium persulfate is 2-4:1-3:150:15-25:10-20:5-10:10-15:0.5-1:5-10:3-6.

7. The preparation method according to claim 1, characterized in that: In step S3, the mass ratio of the antibacterial fiber to the composite emulsion is 1:10-15.

8. The preparation method according to claim 1, characterized in that: In step S4, the mass ratio of the composite fiber to the genipin solution is 1:15-25, and the mass fraction of the genipin solution is 0.4-0.6%.

9. The preparation method according to claim 1, characterized in that: In step S4, the temperature of the heat curing treatment is 50-70° C., and the time of the heat curing treatment is 2-3 hours.

10. The antibacterial linear drawstring material for tampons prepared by the preparation method according to any one of claims 1 to 9.

Citation Information

Cited By

  • Tampon integrating sewing thread and pull rope

    CN120203932A